In Vitro Activity of "Old" and "New" Antimicrobials against the Klebsiella pneumoniae Complex - Alicja Sękowska (MDPI AG, 2024)
The Klebsiella pneumoniae complex is a commonly isolated bacteria in human infections. These opportunistic pathogens pose a serious threat to public health due to their potential transmission to the human population. Resistance to carbapenems is a significant antimicrobial resistance mechanism, leading to limited therapeutic options. Therefore, the aim of this study was to evaluate the in vitro activity of fosfomycin, colistin, ceftazidime-avibactam, and meropenem-vaborbactam against multidrug-resistant K. pneumoniae complex strains. This study involved 160 strains of Gram-negative rods, comprising 138 K. pneumoniae and 22 K. variicola. The minimal inhibitory concentration of fosfomycin was estimated using the agar dilution method, and for colistin, the microdilution method was employed. Susceptibility to ceftazidime-avibactam and meropenem-vaborbactam was determined using the gradient strip method. All analyzed K. pneumoniae complex isolates produced extended-spectrum β-lactamases, and 60.0% exhibited carbapenemases. The majority of the analyzed strains were susceptible to fosfomycin and colistin (62.5%). Among pandrug-resistant K. pneumoniae complex isolates, the highest susceptibility was observed with colistin (43.9%). Fosfomycin demonstrated good activity against ESβLs- and VIM-positive isolates from this complex. Colistin also exhibited satisfactory in vitro activity against VIM- and KPC-positive isolates from the K. pneumoniae complex. Ceftazidime-avibactam displayed good activity against K. pneumoniae complex strains producing ESβLs, KPC, and OXA enzymes. Additionally, meropenem-vaborbactam showed satisfactory in vitro activity against ESβLs- and KPC-positive isolates from this complex.